The Liability of Unilateral Termination by Government on Goods and Service Procurement Contract - Anton Cahyono; Ninis Nugraheni; Mokhamad Khoirul Huda (Fakultas Hukum Universitas Hang Tuah, 2018)
The increasing development in Indonesia, particularly the development of public facilities and infrastructures makes many public contracts, commonly called governmental goods and service contract, increase as well. It is a contract which one of the parties involves the government. In Indonesia, goods and service procurement contracts are not always well-conducted as expected. Lawsuits, which one of those is the liability from one party, may reveal in such contracts. Therefore, this study would discuss about an issue of unilateral contract termination on good-and-service procurement contract along with its solution. Referring to legal regulation related to governmental good-and-service procurement contract, President’s Regulation No. 54 Year 2010 on Governmental Goods and service Procurement and had been amended by President’s Regulation No. 4 Year 2015 about the Forth Amandment of President’s Regulation No. 54 Year 2010 about Governmental Goods and service Procurement.